Estraneità, ospitalità, traduzione. Per una filosofia della migrazione - Elena Siclari (Democrazia e Diritti Sociali)
Migration brings with it an ethical and legal challenge to which it is increasingly complex to provide answers. From these pages emerges a philosophy of migration that takes the form of a true hermeneutics of the interhuman bond. The contribution aims to offer a vision of the migration phenomenon not as a problem of reception but as a starting point from which to reflect on the categories of otherness and in particular on the figure of the foreigner thanks to the study of some of the major philosophers (Heidegger, Jullien, Ricœur) who have expressed themselves on the themes of identity, hospitality and translation understood as a hermeneutic paradigm between different cultural worlds.